Communicative Exercises to Practice the Simple Present Tense in 10 TH Grade, at “Reinaldo Urquiza Ceballos” High School - Gómez Gutierrez, Dianirys (Universidad Central "Marta Abreu" de Las Villas. Facultad de Educación Media. Departamento de Lenguas Extranjeras., 2018)
The teaching of English in High School is one of the objectives of the Cuban Educational System and speaking, the main ability to be developed. Everyday, teachers face several situations that hinder the students’ proper development in the English language and among these problems; grammar is one of the most troublesome aspects of language. The present participant action research was carried out in 10 th grade, Class D at ‘’Reinaldo Urquiza Ceballos’’ High school. It aimed at improving students’ grammar as a way to back up the development of the speaking ability.In order to achieve this goal, some theoretical methods were administered to gather the necessary information about the treatment given to the speaking ability with emphasis on the teaching of grammar, as well as some empirical methods to diagnose the current situation in the study group . As a result, some changes in the teaching learning process of English were implemented in order to know the possible transformations occurred in the subjects of research and with that data build up a final scientific result. After finishing this process, The scientific result that emerged was a system of five lessons with two communicative exercises each one, all of them aim at dealing with the third person singular and the forms of the verb to be in the simple present tense to back up the development of the speaking ability.

L'enseignement de l'anglais à l'école secondaire est l'un des objectifs de l'éducation cubain et de la parole, la principale capacité d'être mis au point. Tous les jours, les enseignants sont confrontés à plusieurs situations qui entravent le bon développement des élèves dans la langue anglaise et parmi ces problèmes, la grammaire est l'une des plus nuisibles aspects de la langue. La présente recherche-action des participants a été effectué en 10ème classe, Classe D à ''Reinaldo Urquiza Ceballos'' High School. Elle vise à l'amélioration de la grammaire des étudiants comme un moyen de sauvegarder le développement de la capacité de parole.Afin d'atteindre ce but, certaines méthodes théoriques ont été administrés pour recueillir les informations nécessaires sur le traitement réservé à la capacité de parler avec l'accent sur l'enseignement de la grammaire, ainsi que des méthodes empiriques pour diagnostiquer la situation actuelle dans le groupe d'étude . En conséquence, certains changements dans le processus d'enseignement et d'apprentissage de l'anglais ont été mis en œuvre afin de connaître les transformations possibles est produite dans les sujets de la recherche et avec les données que construire un résultat scientifique final. Après avoir terminé ce processus, le résultat scientifique qui s'est dégagé est un système de cinq leçons avec deux exercices de communication chacun, tous d'entre eux visent à faire face à la troisième personne du singulier et les formes du verbe être dans le temps présent simple pour sauvegarder le développement de la capacité de parole.
Keywords: Inglés; Enseñanza de Lenguas; Aprendizaje de Lenguas